The SCARE 2020 Guideline: Updating Consensus Surgical CAse REport (SCARE) Guidelines. (December 2020) - Agha, Riaz A.; Franchi, Thomas; Sohrabi, Catrin; Mathew, Ginimol; Kerwan, Ahmed; Thoma, Achilles; Beamish, Andrew J.; Noureldin, Ashraf; Rao, Ashwini; Vasudevan, Baskaran; Challacombe, Ben; et al.
Abstract: Introduction: The SCARE Guidelines were first published in 2016 and were last updated in 2018. They provide a structure for reporting surgical case reports and are used and endorsed by authors, journal editors and reviewers, in order to increase robustness and transparency in reporting surgical cases. They must be kept up to date in order to drive forwards reporting quality. As such, we have updated these guidelines via a DELPHI consensus exercise. Methods: The updated guidelines were produced via a DELPHI consensus exercise. Members were invited from the previous DELPHI group, as well as editorial board members and peer reviewers of the International Journal of Surgery Case Reports. The expert group completed an online survey to indicate their agreement with proposed changes to the checklist items. Results: A total of 54 surgical experts agreed to participate and 53 (98%) completed the survey. The responses and suggested modifications were incorporated into the new 2020 guideline. There was a high degree of agreement amongst the SCARE Group, with all modified SCARE items receiving over 70% scores 7–9. Conclusion: A DELPHI consensus exercise was completed and an updated and improved SCARE Checklist is now presented. Highlights: This was a DELPHI consensus exercise to update the SCARE guidelines. Of the invited surgical experts, 53 (98%) completed the survey. There was a high level of agreement within the SCARE Group. The survey responses were incorporated as modifications, and an improved SCARE Checklist is now presented for use.